Kiskeya palassaina, new genus and new species of Saicinae (Heteroptera: Reduviidae) from the Dominican Republic - Weirauch, Christiane; Forero, Dimitri (Zootaxa, 2007)
A new genus and a species of Saicinae, Kiskeya palassaina, n. gen., n. sp., are described from the Dominican Republic. The armature of the fore leg of the nine apterous female specimens are unique among genera of Saicinae in consisting of spines on the fore femur, but of stiff setae on the fore tibia. A key to the New World genera is given. Digital macrophotographs, scanning electron micrographs, and illustrations are provided.